A Cross-cultural Examination of the Noise-sensitivity Scale-short Form: Measurement Invariance Testing between the US and Chinese Samples - Miller, Z.; Huang, J.; Costigan, H.; Luo, J.; Deng, H.; Xu, X.; Taff, B.; Sun, C.; Yang, X.; Wang, Z.; Lin, D.; Qu, S.; et al. (Elsevier Ltd, 2018)
No Abstract Available